2022
DOI: 10.1088/1757-899x/1214/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Holistic eco-design tool within automotive field

Abstract: In the last decades, sustainability has become a critical issue for the vehicle industry. Today automotive manufacturers are subjected to several government regulations aimed at making the industry more environmentally sustainable. In this context, many research and industrial activities are focused on the eco-design field by developing innovative materials, novel manufacturing technologies, and new methodology; the main objective is to combine the best design performance with increased environmental responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although there is a variety of literature describing the various dimensions of sustainability and its metrics (more than 300,000 articles), to the best of the authors' knowledge based on their in-depth research, there is no systematic method for identifying the indicators of sustainable production that are relevant to product lifecycle management in the automotive industry. The main groups of articles tackle the issues of sustainability aspects indicators [19][20][21][22], automotive industry aspects indicators [8][9][10][23][24][25][26], and product lifecycle management aspects indicators [6,10,23,[27][28][29][30], but there is a lack of papers connecting all of those issues. Additionally, the majority of the literature on sustainability indicators discusses industries related to energy, construction, and agriculture [31][32][33][34][35].…”
Section: Significance and Aimmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is a variety of literature describing the various dimensions of sustainability and its metrics (more than 300,000 articles), to the best of the authors' knowledge based on their in-depth research, there is no systematic method for identifying the indicators of sustainable production that are relevant to product lifecycle management in the automotive industry. The main groups of articles tackle the issues of sustainability aspects indicators [19][20][21][22], automotive industry aspects indicators [8][9][10][23][24][25][26], and product lifecycle management aspects indicators [6,10,23,[27][28][29][30], but there is a lack of papers connecting all of those issues. Additionally, the majority of the literature on sustainability indicators discusses industries related to energy, construction, and agriculture [31][32][33][34][35].…”
Section: Significance and Aimmentioning
confidence: 99%
“…An analysis of different sectors showed that the automotive industry is crucial from an environmental point of view-according to a publication by the United Nations Environment Programme (UNEP) referring to the "Resource Efficiency and Climate Change: Material Efficiency Strategies for a Low-Carbon Future" report, "producing and using materials more efficiently to build passenger cars and residential homes could cut CO 2 equivalent emissions between 2016 and 2060 by up to 25 gigatons across the Group of Seven (G7) member states" [37]. According to Hertwich et al, road transport contributes heavily to the overall environmental impact, as it causes approximately 20% of greenhouse gas (GHG) emissions [24]. The European Commission in the "sustainable and smart" mobility strategy is expecting to have at least 30 million zero-emission cars on European roads by 2030 [25].…”
Section: Automotive Industry Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10], Ajanovic A., Haas R. [11], Antonacci A., Del Pero F., Baldanzini N., Delogu M. [12] in their works form the foundations of the importance of the concept of sustainable development for the successful transition of the transport system to a new level of functioning, laying the foundations for a further increase in the importance of this concept in the marketing activity of automotive companies. In the works of Arefieva O.V.…”
mentioning
confidence: 99%